Organic thin film formation using asymmetric surface-active viologens - Shrestha, Nabeen K (Langmuir : the ACS journal of surfaces and colloids, 2007)
In the present study, asymmetric surface-active viologens were applied successfully for the thin film formation of organic pigments using the immersion plating technique. The influences of the hydrophobicity of the surfactants and the pH of the plating solution on the film formation were investigated. In addition, the interfacial chemistry and electrochemistry of the surfactants were studied, and the mechanism of the film formation has been proposed and discussed